Ultrasound shows swollen joints are the better proxy for synovitis than tender joints in DMARD-naïve early psoriatic arthritis. Issue 3 (15th November 2021) - Dubash, Sayam R; Alabas, Oras A; Michelena, Xabier; Garcia-Montoya, Leticia; De Marco, Gabriele; Merashli, Mira; Wakefield, Richard J; Emery, Paul; McGonagle, Dennis; Tan, Ai Lyn; Marzo-Ortega, Helena
Abstract: Objective: To evaluate the relationship between clinical examination/US synovitis in DMARD-naïve early PsA. Methods: Eligible patients underwent matched clinical/US 44-joint assessment for tender and/or swollen joints (TJ/SJ) and US synovitis [grey scale (GS) ≥ 2 or power Doppler (PD) ≥ 1]. Statistical agreement between TJ/SJ, GS ≥ 2 and PD ≥ 1 was calculated by prevalence-adjusted and bias-adjusted κ (PABAK). To derive probabilities of GS ≥ 2/PD ≥ 1, mixed-effects logistic regression-modelled odds of US synovitis in TJ/SJ were conducted. Results: In 155 patients, 5616 joints underwent clinical/US examination. Of these joints, 1039 of 5616 (18.5%) were tender, 550 of 5616 (9.8%) were swollen, 1144 of 5616 (20.4%) had GS ≥ 2, and 292 of 5616 (5.2%) had PD ≥ 1. GS ≥ 2 was most prevalent in concomitantly tender and swollen joints [205 of 462 (44%)], followed by swollen non-tender joints [32 of 88 (36.4%)], tender non-swollen joints [148 of 577 (25.7%)] and non-tender non-swollen joints (subclinical synovitis) [759 of 4489 (16.9%)]. Agreement between SJ/PD ≥ 1 was high at the individual joint level (82.6–96.3%, PABAK 0.65–0.93) and for total joints combined (89.9%, PABAK 0.80). SJ/GS ≥ 2 agreement was greater than between TJ/GS ≥ 2 [73.5–92.6% vs 51.0–87.4% (PABAK 0.47–0.85 vs PABAK 0.35–0.75), respectively]. Swelling was independently associated with higher odds of GS ≥ 2 [odds ratio (OR) (95% CI); 4.37 (2.62, 7.29); P < 0.001] but not tenderness [OR = 1.33 (0.87, 2.06); P = 0.192]. Swelling [OR = 8.78 (3.92, 19.66); P < 0.001] or tenderness [OR = 3.38 (1.53, 7.50); P = 0.003] was independently associated with higher odds of PD ≥ 1. Conclusion: Synovitis (GS ≥ 2 and/or PD ≥ 1) was more likely in swollen joints than in tender joints in DMARD-naïve, early PsA. Agreement indicated that swollen joints were the better proxy for synovitis, adding to greater understanding between clinical and US assessments.